IMPLEMENTATION OF PUBLIC RELATIONS MODEL IN SOSIALIZING LOCAL CULTURE TO SUMENEP'S YOUNG GENERATION - Mohammad Insan Romadhan; Afifatur Rohimah; B.C.S Adhi Pradana (Metakom, 2019)
The globalization era is driving the decline of Indonesia's local cultural extension, especially in the millennial generation. The real impact of the phenomenon that occurs the worst possibility is the extinction of local culture due to the absence of a millennial generation of the local culture. It is the duty of the government to take these issues seriously, so researchers are interested in reviewing the implementation of the public relations model in socializing local culture to the millennial generation in Sumenep. The theoretical study uses the public relations model of Grunig & Hunt. The research approach uses qualitative descriptive research. The informant in the research head of the field of promotion of the Department of Tourism, Culture, Youth and Sports and several millennial generations in Sumenep. The results of the study showed that the socialization carried out tended to implement the Public Information Model.